Blended learning module for a course in statistics / Rohana Yusoff, Nur Hidayah Md Noh, Sarah Yusoff - Yusoff, Rohana; Md Noh, Nur Hidayah; Yusoff, Sarah (Penerbit UiTM (UiTM Press), 2015)
Instructors for mathematical and statistical courses generally feel that it is quite impossible to have an effective teaching and learning process if the blended learning teaching style were to be adopted. The traditional teaching instruction of ‘chalk and talk’ still has many proponents. To find out the truth of this conjecture, we experimented with 298 students who had enrolled for Introduction to Statistics course at a public university in Malaysia. We had enrolled the course as Blended Learning with the Institute of Learning and Quality Management (ILQAM) at the beginning of the semester (May-October 2014). A video power point for each chapter of the course syllabus was developed and a detailed blended learning scheme of work was outlined to the students. Students were assessed using online quizzes, written quizzes, written tests, and final examination. Two hours of the total four contact hours per week was allocated to students’ Self-Learning while the other two hours was allocated to Assisted-Learning sessions.